Implementing Ac-225 labelled radiopharmaceuticals: practical considerations and (pre-)clinical perspectives - Eline L. Hooijman; Valery Radchenko; Sui Wai Ling; Mark Konijnenberg; Tessa Brabander; Stijn L. W. Koolen; Erik de Blois (SpringerOpen, 2024)
Abstract Background In the past years, there has been a notable increase in interest regarding targeted alpha therapy using Ac-225, driven by the observed promising clinical anti-tumor effects. As the production and technology has advanced, the availability of Ac-225 is expected to increase in the near future, making the treatment available to patients worldwide. Main body Ac-225 can be labelled to different biological vectors, whereby the success of developing a radiopharmaceutical depends heavily on the labelling conditions, purity of the radionuclide source, chelator, and type of quenchers used to avoid radiolysis. Multiple (methodological) challenges need to be overcome when working with Ac-225; as alpha-emission detection is time consuming and highly geometry dependent, a gamma co-emission is used, but has to be in equilibrium with the mother-nuclide. Because of the high impact of alpha emitters in vivo it is highly recommended to cross-calibrate the Ac-225 measurements for used quality control (QC) techniques (radio-TLC, HPLC, HP-Ge detector, and gamma counter). More strict health physics regulations apply, as Ac-225 has a high toxicity, thereby limiting practical handling and quantities used for QC analysis. Conclusion This overview focuses specifically on the practical and methodological challenges when working with Ac-225 labelled radiopharmaceuticals, and underlines the required infrastructure and (detection) methods for the (pre-)clinical application.